Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,3\left(x-12\right)-2\left(2x-4\right)=3-2\left(x-11\right)\)
\(3x-36-4x+8=3-2x+22\)
\(3x-4x+2x=3+22+36-8\)
\(x=53\)
\(a,3\left(x-12\right)-2\left(2x-4\right)=3-2\left(x-11\right)\)
\(3x-36-4x+8=3-2x+22\)
\(3x-4x+2x=3+22+36-8\)
\(x=53\)
\(b,5\left(x-7\right)-4\left(x-8\right)=5-2\left(x-4\right)+2x\)
\(5x-35-4x+32=5-2x+8+2x\)
\(5x-4x+2x-2x=5+8+35-32\)
\(x=16\)
a)\(\frac{x+11}{x-6}=\frac{x-6+17}{x-6}=\frac{x-6}{x-6}+\frac{17}{x-6}\)
=>x-6\(\in\) Ư(17)
x-6 | 1 | -1 | 17 | -17 |
x | 7 | 5 | 23 | -11 |